The Development of an English Nursing Textbook Oriented Towards Localization and Globalization to Improve Students' Vocabulary for Vocational High School (Lembaran Ilmu Kependidikan, 2025)
This research is motivated by the ineffectiveness of the implementation of the textbooks used which causes a lack of vocabulary knowledge of students in the field of nursing. The purpose of this study is to produce a practical nursing English textbook used in the learning process at SMKS Kesehatan Mutiara Mandiri Sungailiat and to find out the effect of textbooks on improving the vocabulary of nursing students. This research is a Research & Development study by applying the ADDIE development model consisting of analysis, design, development, implementation, and evaluation. The data collection method uses a questionnaire. The population of this study were class XI A students as the experimental group and class XI C students as the control group. The results of the validation of the "Smart English for Nursing" textbook showed that several experts gave an assessment with good qualifications. While the average practicality test conducted by students and teachers was categorized as practical. In addition, the textbook has been applied by teachers to students in the learning process in class. This textbook is able to improve the vocabulary knowledge of nursing students. This is evidenced by the Sig. value data of 0.000